Digital storytelling book approach on Tok Gajah history / Mohamad Akmal Jamalludin - Jamalludin, Mohamad Akmal (2022)
Illustration digital storytelling book publishing will give benefit to all the readers. The publication of a Illustration book approach on Tok Gajah history will provide the information to the public either book lover or history lover about this history figure which is one of the independence fighter for the our country to achieve the independence from colonialism. History is subjective, there are some people like to get more knowledge about it and there are people who think history was not very interesting matter. Nowadays, based on the observation of researchers see what happens to people around in Malaysia, People are more likely to follow and know the trending thing than knowing things that have long been as historical story. To make history become attractive and more relevant for current generation, which is by making digital storytelling (E-book) with illustration elements one of the strategies to make history become more interesting and follow nowadays trend. The problem for these issues was about the suitable of ideas which is the readaptation story one of history figure such as Tok Gajah as Digital illustration book. The book will be the reading material to increase the knowledge and exposure about Tok Gajah history to the public knowledge. The concept and layout design of the book will play the important role to get the attention of the reader and effectiveness to understanding the story contained in the book. The drawing style of illustrations for the book also effect the readers, because it will be the main interest point for the readers. The research was conducted using several methods such as quantitative and exploratory method to fill the data collection.